Analyzing the Pattern of Spatial Interactions of Nomads with Emphasis on the Flow of People (Case study: Babadi Ecosystem of Bab Bakhtiari Tribe) - Vahid Riahi; Farzad Mahmoudiyan; Farhad Azizpour (برنامه ریزی فضایی, 2022)
Statement of the Problem: Interactions and spatial flows are within and outside the territory among different life patterns (between cities, villages, and nomadic spatial actors) at the level of geographical areas, including nomadic ecosystems. In this regard, interactions and development of nomadic ecosystems affect both sides of heterogeneous areas form a level of spatial integration, and provide a platform for innovation and creativity for sustainable spatial development planning.Purpose: The present study, in the framework of the network paradigm with emphasis on the regional network approach, seeks to analyze the patterns of spatial interactions in the nomadic ecosystem of the Babadi Bab Bakhtiari tribe.Methodology: The present research was applied and descriptive-analytical in terms of purpose and method. The method of data collection according to the nature of the research was library and field visits based on the number of spatial actors (summer-winter quarters) at the ecological level. The required data were collected using a questionnaire and the questioning technique. Then, the spatial network analysis method (which is based on the social network analysis method) was used. In the framework of this method, the basic criteria of analysis are based on the framework of socio-spatial criteria (location, distance, scale, and power). The UCINET software was also used for data analysis.Results: Based on the findings and the four criteria studied by socio-spatial actors in the ecosystem, spatial interaction patterns lacked integration. In this sense, the division of spatial labor has been spontaneous (without planning) in such a way that the flow center of the people is limited. Therefore, the middle centers (Mianbandha) ranked first and the cities of Chelgard, Farsan, Lali, and Sheikh Ali Khanranks ranked second, third, fourth, and fifth in the patterns of spatial interactions inside and outside the socio-spatial bio-realm. Influenced by the type and nature of the flow of people, the daily migration of nomads is subject to the centralized pattern (single-center) and one-way spatial interactions, and the seasonal migration of nomads follows the decentralized pattern (multi-center) and two-way spatial interactions. The later migration is far from the pattern of network spatial interactions because in most spatial actors, two-way links are established apparently.Innovation: In this study, the analysis of spatial interaction patterns affected by the type and nature of people within the nomadic ecosystem and the relationship of the entire ecosystem with cities and villages, was considered spatially. In addition, following the discovery of the visible and hidden relationships of spatial actors of the nomadic ecosystem, people flow indices are categorized under the conceptual relationships of the combined elements of human relationship geography and social networks in order to analyze spatial interaction patterns in a dynamic network. Keywords: Spatial Interactions, Spatial Flow, Nomadic Ecology, Babadi Bab. References- Allen, J., & Cochrane, A. (2007). Beyond the territorial fix: Regional assemblage, politics and power. Journal of Regional Studies, 41(9), 1161–1175.- Anderson, B., & McFarlane, C. (2011). Assemblage and geography. Area, 43(2), 124–127.- Bodin, O., & Crona, B. I. (2009). The role of social networks in natural resource governance: What relational patterns make a difference?. Journal of Global Environmental Change, 19(3), 366–374.- Borgatti, S. P. (2005). Centrality and network flow. Journal of Social Networks, 27(1), 55–71.- S. P., Mehra, A., Brass, D. J., & Labianca, G. (2009). Network analysis in the social sciences. Science, 323(5916), 892–895.- Brandes, U., & Erlebach, T. (2005). Network analysis: Methodological foundations. Springer-Verlag Berlin Heidelberg.- Castells, M. (2009). Communcation power. UK: Oxford University Press.- Christaller, W. (1933/1966). Die Zentralen Orte in Süddeutschland. Jena: Gustav Fischer Verlag; Translated by Baskin, C. W. Englewood Cliffs, NJ: Prentice-Hall.- Douglass, M. (1998). A regional network strategy for reciprocal rural-urban linkges: An agenda for policy research with refrence to Indonesia. Journal of Third World Planning Review,  20(1), 1–34.- Douglass, M. (1999). Rural-urban integration and regional economic resilience: Strategies for the rural-urban transition in Northeast. (n.p).- M. (1983). The strength of weak ties: A network theory revisited. Sociological Theory, 1, 201–233.- Gregory, D., Johnston, R., & Whatmore, S. (2009). The dictionary of human geography. Fifth Edition. West Sussex: A John Wiley & Sons, Ltd.- Hadjimichalis, C., & Hudson, R. (2006). Networks, regional development and democratic control. International Journal of Urban and Regional Research, 30(4), 858–872.- Haggett, P. (2001). Geography: A global synthesis. Pearson Education.- Haggett, P., & Chorley, R. J. (1970). Network analysis in geography. New York: St Martin’s Press.- Hansen, D. L., Shneiderman, B., & Smith, M. A. (2011). Analyzing social media networks with nodeXL: Insights from a connected world. Morgan Kaufmann.- M. (2004). Spatial relationships? Towards a reconceptualization of embedded ness. Journal of Progress in Human Geography, 28(2),165–186.- Hetherington, K., & Law, J. (2000). After networks. Environment and Planning D: Society and Space, 18(2), 127–132.- Hudson, R. (2001). Producing places. New York: Guilford Press.- Lefebvre, H. (1991). Critique of everyday life. Translated by John Moore. New York: Verso Books.- Liu, Y.,  Sui, Z., Kang, C., & Gao, Y. (2014). Uncovering patterns of inter-urban trip and spatial interaction from social media check-in data. Plos One, 9(1), e86026.- Massey, D. (1994). Space, place, and gender. Minneapolis, MN: University of Minnesota Press.- Newman, M. E. J. (2003). The structure and function of complex networks. SIAM Review, 45(2), 167–256.- Nye Jr, J. S. (2008). Public diplomacy and soft power. The Annals of the American Academy of Political and Social Science, 616(1), 94–109.- Pacione, M. (2005). Urban geography: A global perspective. Second Edition. London: Routledge.- Pitzl, G. R. (2004). Encyclopedia of human geography. First Edition. Westport, Connecticut: Greenwood Press.- Portnov, B. A., & Pearlmutter, D. (1999). Sustainable urban growth in peripheral areas. Journal of Progress in Planning, 52(4), 239–308.- Pred, A. (1984). Place as historically contingent process: Structuration and the time-geography of becoming places. Annals of the Association of American Geographers, 74(2), 279–297.- Ramirez, B. (2009). Core-periphery models. In: Kitchin, R., & Thrift, N. (Eds.) International Encyclopedia of Human Geography. Vol. 2. Elsevier Ltd, pp. 286- 291.- Retaille, D. (2013). From nomadic to mobile space: A theoretical experiment (1976–2012). Nomadic and Indigenous Spaces Productions and Cognition, 55-75.- Scott, J. (2011). What is social network analysis?. New York, NY: Bloomsbury Academic.- Simonsen, K. (2004). Networks, flows, and fluids—reimagining spatial analysis?. Environment and Planning A, 36(8), 1333–1337.- Skillicorn, D., Walther, O., Zheng, Q., & Leuprecht, C. (2018). Spatial and temporal diffusion of political violence in North and West Africa. In: Walther O., & Miles W. (Eds.) African Border Disorders. London: Routledge, pp. 87-112.- Smith, C. J. (1980). Social networks as metaphors, models and methods. Journal of Progress in Human Geography, 4(4), 500–524.